Deviation analysis in safety using iPhone application / Muhamad Yusrin Ya'acob - Ya'acob, Muhamad Yusrin (2014)
This thesis presents deviation analysis in safety by using iPhone application for a company called Alstom. The present application to do analysis of deviation is by using Microsoft Excel but it is difficult in this method for the safety officer to do the analysis because all data must be recorded on piece of paper before transferred to the computer. Besides that, the present method consume resources such as time and paper, hence it is not user friendly. The software used to develop the mobile application is by using Xcode 5.1 that is only available on OS X and not compatible with Windows operating system. The programming language used in the project is C-Objective. The results for this project are the mobile application is able to plot the bar chart from the iPhone based on 14 categories of deviation. Besides that, the user is able to send the recorded bar chart into the email at Alstom. Therefore, the user can do the analysis of deviation by enter the number of deviation at the workplace based on respective categories and send the information via the email.